A New Approach on Making European Agriculture More Efficient under Uncertainty Conditions - Romeo Victor Ionescu; Monica Laura Zlati; Valentin Marian Antohi (Agronomy, 2022)
Agriculture is a strategic sector of the European economy in the current economic, social, climatic, and geo-political conditions generated by global crisis and the war in Ukraine. The main objective of the research is to quantify the vulnerabilities of EU agricultural evolution and to assess the opportunities for development through the building of a scoreboard of viable agricultural development solutions in line with the needs expressed in the current unfavourable context. The importance of this research is related to smart agriculture as a solution to the food crisis generated by the same uncertainty conditions. The methods used are empirical literature review and econometric modelling of vulnerabilities based on the dynamic evolution of branch efficiency and effectiveness indicators under exogenous events (economic crisis, geo-political crisis, soil and climate crisis, health crisis), collected from official data sources. The outcome of the study is the identification of viable, implementable solutions to ensure the planned success of the sustainable development of the branch.